Sustainability nudges in the context of customer co-design for consumer electronics - Stephan Hankammer; Robin Kleer; Frank T. Piller (Journal of Business Economics, 2020)
In this study, we shed light on the unexplored potential of customer co-design in a mass customization (MC) setting to contribute to the promotion of sustainable consumption. We theoretically derive and empirically test several opportunities for companies to improve sustainable consumption and production in a joint effort with consumers. Our research bridges between the MC and the sustainability literature and shows that MC enables consumers to cohere attitude and action, based on individual sustainability preferences. We empirically assess whether MC companies can nudge their customers successfully towards more sustainable choices by designing sustainability-based starting solutions (Study 1) and by providing transparent sustainability information (Study 2) in MC configuration systems. We do so by portraying a simulated online buying process of a customizable TV with a realistic web-based product configurator. We find that sustainable defaults can play a significant role in promoting sustainable consumption, while providing detailed sustainability information does not show an effect. To get more insights into our results, we discuss the results on a supplementary qualitative analysis based on think-aloud consumer tests (Study 3), revealing several suggestions for further research. Using these findings, we revisit sustainability information in Study 4 and find that intuitive labels significantly influence consumers to choose more sustainably.
Keywords: M14; M39; Q01; Q59; 650; Mass customization; Sustainability; Customer co-design; Consumer choice; Nudging; Product configurator